Symmetry Analysis and Wave Solutions of the Fisher Equation Using Conformal Fractional Derivatives - Shalu Saini; Rajeev Kumar; null Deeksha; Rishu Arora; Kamal Kumar (Journal of Applied Mathematics)
In the present article, the time fractional Fisher equation is considered in conformal form to study the application of the Lie classical method and quantitative analysis. The Lie symmetry method has been applied to find the infinitesimal generators and symmetry reductions of the fractional Fisher equation. The obtained reduced form of the equation is solved by the method of G′/G, which gives different forms of solutions. The theory of bifurcation has been utilized in the reduced form to check the stability and nature of critical points by transforming the equations into an autonomous system. Some phase portraits have been drawn at different critical points by the use of maple.